Bullying; A Psychosocial Stressor - Yusra Saleem; Shamoon Noushad; Shahana Urooj Kazmi; Salman Shaikh; Nabeela Noor; Mariyam Asim (Annals of Psychophysiology, 2018)
Background: The bullying incidences have been increasing in the past few years resulting in a number of psychosocial traumas including depression, anxiety, violence and many other health concerns. Despite being a global issue, not a large number of studies have addressed this distressing act. This social threat causes negativity on both sides whether the victim or the perpetrator. The aim of the study was to evaluate the prevalence of this psychosocial stressor, its associated characteristics and bullying perceptions among the study population.